Fairground Attractions A Genealogy of the Pleasure Ground - Philips, Deborah (Bloomsbury Academic, 2012)
This book is available as open access through the Bloomsbury Open Access programme and is available on www.bloomsburycollections.com. The study investigates the cultural production of the visual iconography of popular pleasure grounds from the eighteenth century pleasure garden to the contemporary theme park. Deborah Philips identifies the literary genres, including fairy tale, gothic horror, Egyptiana and the Western which are common to carnival sites, tracing their historical transition across a range of media to become familiar icons of popular culture.Though the bricolage of narratives and imagery found in the contemporary leisure zone has been read by many as emblematic of postmodern culture, the author argues that the clash of genres and stories is less a consequence of postmodern pastiche than it is the result of a history and popular tradition of conventionalised iconography.